Habilidades de la motricidad fina en pacientes pediátricos con parálisis cerebral - Neivis Torriente Herrera; Marianne Sanchez Savigñon; Alexander Echemendia del Valle; Niurka Teresita Marrero Santana (Medimay)
Introducción: